Noise effects and the impact of detector responses on the characterization of extreme ultraviolet attosecond pulses - Hu, Shuyuan; Hartmann, Maximilian; Harth, Anne; Ott, Christian; Pfeifer, Thomas (Applied optics, 2020)
We employ numerical simulations to study the effects of noise on the reconstruction of the duration and satellite intensity ratio for transform-limited single and double pulses of 200 as duration. The forms of noise we implement are delay jitters between the attosecond pulse and the near-IR laser field, energy resolution of the photoelectron detector, and Poisson noise in streaking spectrograms with different count levels. We use the streaking method to characterize the pulse and the extended ptychographic iterative engine retrieval algorithm to reconstruct the pulse from the simulated streaking spectrogram. We found that, for practical purposes, when implementing a combination of all three mentioned noise contributions, the attosecond pulse duration will be overestimated when the photoelectron count level is low. Furthermore, the satellite pulse amplitude of the attosecond double pulse can be retrieved within 10% accuracy.
Gesehen am 02.12.2020